Penerapan Metode Belajar Cooperative Learning untuk Meningkatkan Kesadaran Beragama Siswa - Fauzan, Fauzan; Dannur, Moh.; Hairit, Artamin; Alfiansyah, Alfiansyah (International Conference on Islamic Studies, 2022)
Religious awareness is a consistency for its adherents and becomes a benchmark for compliance with religious principles which are imprinted in individual strengths outside of their awareness that shape behavior, thoughts, feelings and actions. Meanwhile, religion has an important role in instilling the consistency of human potential in building the social construct of society. Individual social potential can be instilled from early age, especially school-age children with theri community that can influence the formation of their potential in family, public and school environment. School is one environment has a dominant power in boosting the social potential of individuals. So the cooperative learning model (cooperative learning) is one model that can be developed in the learning process in schools, especially in increasing individual religious awareness in a social context.